2019
DOI: 10.1002/pi.5815
|View full text |Cite
|
Sign up to set email alerts
|

Free volume defects and transport properties of mechanically stable polyhedral oligomeric silsesquioxane embedded poly(vinyl alcohol)‐poly(ethylene oxide) blend membranes

Abstract: Polymer membrane based gas transport and pervaporation processes are fast growing areas in separation technology and have received wide attention as areas of 'clean technology'. Mechanically stable novel polyhedral oligomeric silsesquioxane (POSS) embedded poly(vinyl alcohol) (PVA)/poly(ethylene oxide) (PEO) blend membranes were prepared by solution blending followed by casting. The addition of carboxymethyl cellulose enhanced the interfacial activities of the PVA and PEO blends. The peripheral organic substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…[ 13 ] And, attraction of the membrane material towards gas molecules is another factor that determines the transport of gas molecules. [ 36 ] Condensability of oxygen and its interaction with the rubber membranes are greater than those of nitrogen. This also supports its improved permeability.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] And, attraction of the membrane material towards gas molecules is another factor that determines the transport of gas molecules. [ 36 ] Condensability of oxygen and its interaction with the rubber membranes are greater than those of nitrogen. This also supports its improved permeability.…”
Section: Resultsmentioning
confidence: 99%
“…In the study, positrons are injected from a radioactive source ( 22 Na) to a few‐tenths of mm interior of the polymer. The details were given in one of our previous works 30 …”
Section: Methodsmentioning
confidence: 99%
“…Poly(etherblock‐amide) (PEBAX® 2533) membrane doped with 30 wt% of PEG‐POSS exhibited simultaneous improvement in selectivity and permeability at 30°C 29 . In our previous work we are reported pervaporation and gas separation performance of PVA‐PEO/POSS membranes 30 . It was observed that PEG‐POSS greatly increased the CO 2 and water selectivity of PVA‐PEO membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The work by Li et al [225] demonstrated the enhancement in permeability and CO 2 /N 2 selectivity of the resulting nanocomposite from 250 barrer to 710 barrer and from 59 to 62, respectively, by functionalizing GO with PEG. A quadrupole-dipole interaction between CO 2 and polar groups is the main mechanism that contributed to this improvement [196,[226][227][228]. Similarly, a quadrupole-dipole interaction also contributes to the binding of CO 2 with many metallic compounds from the transition group, especially zinc, cobalt, copper and titanium [229][230][231] and nanomaterials that are rich with electronegative groups such as silica, titanium dioxide (TiO 2 ), GO and BN [32,124,208,232,233].…”
Section: Enhancing Gas Separation Performancementioning
confidence: 99%
“…• commonly conducted via FTIR to detect formation of new bonds between nanofillers and polymer matrix. [192,[194][195][196] 2. visually observe nanofiller-membrane matrix interfaces:…”
mentioning
confidence: 99%